Framework For Integrating ICT Into The Teaching Of Mathematics In School - Chong, Chee Keong (2006)
The purpose of this study is to find out the level of use of ICT among mathematics teachers, their level of integration of ICT into mathematics lessons, the support and the professional development programme needed by them.